Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2018 Symposium - National Academy of Engineering (The National Academies Press, 2019)
This volume presents papers on the topics covered at the National Academy of Engineering's 2018 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2018 symposium was held September 5-7 and hosted by MIT Lincoln Laboratory in Lexington, Massachusetts. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2015 Symposium - National Academy of Engineering (The National Academies Press, 2016)
This volume presents papers on the topics covered at the National Academy of Engineering's 2015 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2015 symposium was held September 9-11 at the Arnold and Mabel Beckman center in Irvine, California. The intent of this book is to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2009 Symposium (The National Academies Press, 2010)
In 1995, the National Academy of Engineering initiated the Frontiers of Engineering Program, which brings together about 100 young engineering leaders at annual symposia to learn about cutting-edge research and technical work in a variety of engineering fields. The 2009 U.S. Frontiers of Engineering Symposium was held at The National Academies' Arnold O. and Mabel Beckman Center on September 10-12. Speakers were asked to prepare extended summaries of their presentations, which are reprinted in this volume. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2005 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2006)
This volume includes 16 papers from the National Academy of Engineering's 2005 U.S. Frontiers of Engineering (USFOE) Symposium held in September 2005. USFOE meetings bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2005 symposium covered four topic areas: ID and verification technologies, engineering for developing communities, engineering complex systems, and energy resources for the future. A paper by dinner speaker Dr. Shirley Ann Jackson, president of Rensselaer Polytechnic Institute, is also included. The papers describe leading-edge research on face and human activity recognition, challenges in implementing appropriate technology projects in developing countries, complex networks, engineering bacteria for drug production, organic-based solar cells, and current status and future challenges in fuel cells, among other topics. Appendixes include information about contributors, the symposium program, and a list of meeting participants. This is the eleventh volume in the USFOE series.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2001 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2002)
This collection includes summaries of presentations given at the NAE Symposium in March 2001. Topics include flight at the leading edge, civil systems, wireless communications, and technology and the human body

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2002 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2003)
This collection includes summaries of presentations given at the NAE Symposium in September 2002. Topics include chemical and molecular engineering in the 21st century, human factors engineering, the future of nuclear energy, and engineering challenges for quantum information technology.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2006 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2007)
This volume includes 15 papers from the National Academy of Engineering's 2006 U.S. Frontiers of Engineering (USFOE) Symposium held in September 2006. USFOE meetings bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2006 symposium covered four topic areas: intelligent software systems and machines, the nano\/bio interface, engineering personal mobility for the 21st century, and supply chain management. A paper by dinner speaker Dr. W. Dale Compton, Lillian M. Gilbreth Distinguished Professor of Industrial Engineering, Emeritus, is also included. The papers describe leading-edge research on commercializing auditory neuroscience, future developments in bionanotechnology, sustainable urban transportation, and managing disruptions to supply chains, among other topics. Appendixes include information about contributors, the symposium program, and a list of meeting participants. This is the twelfth volume in the USFOE series.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2004 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2005)
This volume includes 14 papers from the National Academy of Engineering's Tenth Annual U.S. Frontiers of Engineering Symposium held in September 2004. The U.S. Frontiers meeting brings together 100 outstanding engineers (ages 30-45) to learn from their peers and discuss leading-edge technologies in a range of fields. The 2004 symposium covered these four areas: engineering for extreme environments, designer materials, multiscale modeling, and engineering and entertainment. Papers in the book cover topics such as scalable mobile robots for deployment in polar climates, the challenges of landing on Mars, thin-film active materials, vascular tissue engineering, small-scale processes and large-scale simulations of the climate system, simulating physically accurate illumination in computer graphics, and designing socially intelligent robots, among others. Appendixes include information about the contributors, the symposium program, and a list of the meeting participants. The book is the tenth in a series covering the topics of the U.S. Frontiers of Engineering meetings.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2008 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2009)
Every year at the U.S. Frontiers of Engineering Symposium, 100 of this country's best and brightest engineers, ages 30 to 45, have an opportunity to learn from their peers about pioneering work being done in many areas of engineering. The symposium gives early career engineers working in academia, industry, and government in many different engineering disciplines an opportunity to make contacts with and learn from individuals they would not meet in the usual round of professional meetings. This networking may lead to collaborative work and facilitate the transfer of new techniques and approaches. It is hoped that the exchange of information on current developments in many fields of engineering will lead to insights that may be applicable in specific disciplines and thereby build U.S. innovative capacity. Different topics are covered each year, and, with a few exceptions, different individuals participate. The four general topics covered at the 2008 meeting were: drug delivery systems, emerging nanoelectronic devices, cognitive engineering, and countering the proliferation of weapons of mass destruction. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2003 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
This volume includes 14 papers from the National Academy of Engineering's Ninth Annual U.S. Frontiers of Engineering Symposium held in September 2003. The U.S. Frontiers meeting brings together 100 outstanding engineers (ages 30-45) to learn from their peers and discuss leading-edge technologies in a range of fields. The 2003 symposium covered these four areas: environmental engineering; fundamental limits of nanotechnology; counterterrorism technologies and infrastructure protection; and biomolecular computing. Papers in the book cover topics such as microbial mineral respiration; water-resource engineering, economics, and public policy; frontiers of silicon CMOS technology; molecular electronics; biological counterterrorism technologies; Internet security; DNA computing by self-assembly; and challenges in programming living cells, among others. A talk by Aerospace Corp. president and CEO William F. Ballhaus, Jr. titled The Most Important Lessons You Didn't Learn in Engineering School is also included in the volume. Appendixes include summaries of the breakout session discussion that focused on public understanding of engineering, information about the contributors, the symposium program, and a list of the meeting participants. The book is the ninth in a series covering the topics of the U.S. Frontiers of Engineering meetings.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2007 Symposium - National Academy of Engineering
U.S. Frontiers of Engineering (USFOE) symposia bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2007 symposium covered engineering trustworthy computer systems, control of protein conformations, biotechnology for fuels and chemicals, modulating and simulating human behavior, and safe water technologies. Papers in this volume describe leading-edge research on disparate tools in software security, decoding the \

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2017 Symposium - National Academy of Engineering (The National Academies Press, 2018)
This volume presents papers on the topics covered at the National Academy of Engineering's 2017 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2017 symposium was held September 25-27 at the United Technologies Research Center in East Hartford, Connecticut. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2019 Symposium - National Academy of Engineering (The National Academies Press, 2020)
This volume of Frontiers of Engineering presents papers on the topics covered at the National Academy of Engineering's 2019 US Frontiers of Engineering Symposium, hosted by Boeing in North Charleston, South Carolina, September 25-27. At the annual 2 1\/2-day event, 100 of this country's best and brightest early-career engineers - from academia, industry, and government and a variety of engineering disciplines - learn from their peers about pioneering work in different areas of engineering. Frontiers of Engineering conveys the excitement of this unique meeting and highlights innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2013 Symposium - National Academy of Engineering (The National Academies Press, 2014)
This volume presents papers on the topics covered at the National Academy of Engineering's 2013 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2013 symposium was held September 19-21 and was hosted by DuPont in Wilmington, Delaware. The topics covered at the 2013 symposium were: designing and analyzing societal networks; cognitive manufacturing: energy: reducing our dependence on fossil fuels; and flexible electronics. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2012 Symposium - National Academy of Engineering (The National Academies Press, 2013)
This volume highlights the papers presented at the National Academy of Engineering's 2012 U.S. Frontiers of Engineering Symposium. Every year, the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and technical work. The 2012 symposium was held September 13-15, and hosted by General Motors at the GM Technical Center in Warren, Michigan. Speakers were asked to prepare extended summaries of their presentations, which are reprinted here. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2010 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This volume highlights the papers presented at the National Academy of Engineering's 2010 U.S. Frontiers of Engineering Symposium. Every year, the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and technical work. The 2010 symposium was held September 23 - 25, and hosted by IBM at the IBM Learning Center in Armonk, New York. Speakers were asked to prepare extended summaries of their presentations, which are reprinted here. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2016 Symposium - National Academy of Engineering (The National Academies Press, 2017)
This volume presents papers on the topics covered at the National Academy of Engineering's 2016 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2016 symposium was held September 19-21 at the Arnold and Mabel Beckman Center in Irvine, California. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2014 Symposium - National Academy of Engineering (The National Academies Press, 2015)
This volume presents papers on the topics covered at the National Academy of Engineering's 2014 US Frontiers of Engineering Symposium. Every year the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and innovations in selected areas. The 2014 symposium was held September 11-13 at the National Academies Beckman Center in Irvine California. The topics covered at the 2014 symposium were: co-robotics, battery materials, technologies for the heart, and shale gas and oil. The intent of this book is to convey the excitement of this unique meeting and to highlight innovative developments in engineering research and technical work.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2011 Symposium - National Academy of Engineering (The National Academies Press, 2012)
The practice of engineering is continually changing. Engineers today must be able not only to thrive in an environment of rapid technological change and globalization, but also to work on interdisciplinary teams. Cutting-edge research is being done at the intersections of engineering disciplines, and successful researchers and practitioners must be aware of developments and challenges in areas that may not be familiar to them. At the U.S. Frontiers of Engineer Symposium, engineers have the opportunity to learn from their peers about pioneering work being done in many areas of engineering. Frontiers of Engineering 2011: Reports on Leading-Edge Engineering from the 2011 Symposium highlights the papers presented at the event. This book covers four general topics from the 2011 symposium: additive manufacturing, semantic processing, engineering sustainable buildings, and neuro-prosthetics. The papers from these presentations provide an overview of the challenges and opportunities of these fields of inquiry, and communicate the excitement of discovery.